Karma Dalam Agama Buddha: Systematic Literature Review - Angela, Shelfia; Partono Nyanasuryanadi; Kabri (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2024)
The concept of Kamma (Karma) embodies the principle of causality, where every action has a corresponding consequence. Buddhism considers the theory of Kamma as a basic principle in its teachings. This research uses the System Literature Review (SLR) method to analyze relevant previous research regarding the concept of karma in Buddhism. Meta-synthesis was carried out to answer the research question, namely what is the concept of karma in Buddhism. The aim of this SLR research is to gain a deeper understanding of Kamma in Buddhism; increasing understanding through literacy studies from ten selected studies; thoroughly examine research and intensity of discussion; and provides evidence that the concept of karma exists in Buddhism. The systematic review carried out was using the PRISMA method, evaluating articles published between 2019 and 2023. Research articles related to karma were obtained by searching using the keyword "karma" together with the keyword "Buddhism" in the Google Scholar search database. Mendeley was used to compile and assess titles and abstracts, thereby identifying and eliminating duplicate articles. The methodology used in this investigation is meta-synthesis as a qualitative systematic review, specifically by analyzing 10 journals that are relevant to the research topic. The initial step involves formulating a research problem, followed by a comprehensive search for existing and related studies that align with the research title, then delving into a thorough analysis of these studies. Data collection techniques involve a non-test approach, where previous studies with similar problems are reviewed to obtain results and draw conclusions. The results of the analysis of 10 related journals concluded that there are various research methods regarding karma in Buddhism. Selected articles from 2019-2023 are in English only. Frequently used keywords according to the VOSviewer application are "Buddhism", "Karma", "Buddhist", "Buddha", and "Rebirth".